THE ANALYSIS OF FINANCIAL STABILITY OF ECONOMIC ENTITIES OF THE LIGHT INDUSTRY OF KAZAKHSTAN TAKING INTO ACCOUNT MODERN TRENDS - А.М. Аkhmetova; M.А. Tleubergenova; К.А. Маdykhanova; R.B. Sadykova; K.S.Ayazhanov (Academic Journal of Physical and Chemical Sciences, 2019)
For the modern Kazakhstan economy, the most topical are the problems of ensuring the economic financial sustainability and competitiveness of industrial enterprises. Given the significant role of light industry in ensuring economic and strategic security, employment of the working population and raising its standard of living in new geopolitical conditions, it is necessary to pay special attention to the development of the industry and provide it with substantial investment support, as is done by leading world countries. The article considers the analysis of the current state of the light industry of the Republic of Kazakhstan, which occupies one of the most important places in the production of socially significant products. In recent years, the industry has experienced a decline, which is accompanied by a decrease in the production index and is associated with a technological lag in production, which adversely affects the competitiveness of products. The study used the techniques and methods of balances, reports, grouping, ranking, coefficients, comparisons, time series.